The first studies on Madhhabs histories and their works (Eurasian Journal of Religious Studies, 2017)
The first studies on Madhhabs started to be published in III-IV centuries of Hijri and these initialworks of the Islam Madhhabs History were used as a main source of this particular article. In this workwe payed attention to the uniqueness of the methods of them and to the problems discussed in thatscientific studies. The each applied different methods and approaches. Moreover, the Hadith about thedivide of Ummah for “seventy three” was a base of this article. Some of the first scholars of the IslamMadhhabs History mentioned about the Hadith, but some did not at all. The reasons of appearance ofdifferent branches and stream of Islam and the formation of Madhhabs among Muslim Ummah once theProphet Mohammed (S.A.W) passed away and why each of them possessed their own view or beliefwere discussed thoroughly by some of pioneer scholars of this realm. Thus, the Islam Madhhabs Historyresearches the separation of Madhhabs, faith-aqidah (belief) problems and their influence to the IslamicWorld and society. In spite of the fact that nowadays, the Islam Madhhabs History is important, thestudies in this realm are not as popular as we would like to. However, there are some works on it, forexample, the article of Turar Tugeluly and Batyrbek Turganbekuly called “Madhhab cognition”, of SmailSeitbekov “The History of Madhhabs”, of Sabri Hizmetli “The History of Madhhabs” and etc. The mainreason of the separation of Muslim Ummah after the death of the Prophet of Islam is the emergence ofdifferent opinions and views of faith. The Hadith about the divide of Ummah for seventy three is alsodiscussed in this work.